Hubungan Antara Faktor Konflik Pribadi Dengan kategori Skikizoprenia Pada Pasien Rawat Inap Di Bangsal - Sukatwo ,-; Margo Utomo (JURNAL LITBANG, 2005)
Bockground : Mental Healthy is condition may be to development physical,intelectual and emotional anyone individual by optimal hirmoniiing with development anyone the other in environment. Sktzofrenia is mental inteiefenceoften happened with incidence rate on the world"about 0,5-0,8 % on year. Appearance of skizofrenia seen lack of abil-ity nurse self, nothing observed self, social fall, drowing self from environment along with halisination or suspicious'is very interference. Much predisposing factor skizofrenia from psikological aspect that is personal conflict. personal conflict happened if person faced to problem or condition is have to decided, but can not decide for self. So this research havepurpose to know how correlation between personal conflict factor with skizofrenia cases at patien hospitalized in shed 3th grade RSJD dr RM Soedjarwadi Klaten mont April- May 2004.Method : Kind this research is descriptive analytic, use method survey with interview by quesioner and use cross sectional design. As population of all patient skizofrenia is hospitalized in shed 3th grade RSJD dr RM Soedjarwadi Klatenmonth April - May 2004 and sample in this research is total of population as much as 34 person.Independen variabel is personal conflict factor, that is : 1)approach-refusal conflict ; 2) approach fold conflict ; 3) refusal fold conflict.Dependen variabel is category skizofrinia, that is : 1)acut ; 2)sub acut; 3)residualResult : From univariat analitic obtained mean of age patient 28 years, man patient 70,6 %. Education patient majority in level SLTP 35,3 %. Patient not married yet 82,4%, patient not work yet 64,7 %, personal conflik factor majority is approach refusal conflict 64,7%, approach fold conflict 17,6 % and refusal fold conflict 14,7 %. Category skizofrenii majority is residual 70,6 %, sub acut 20,6 % and acut 8,8 %. From bivariat anilitic with assosiatif test use coefisien contingenti (C) obtained C = 0,524, x2 count 12,841 with approx significansi (p) = 0,012. At a= 5 % with df :=4 obtained x2 table= 9,448. Because p =0,012 <a:0,05 and x2 count= 12,841 > x2 table= 9,449 so that can mean there is significan correlation between personal conflict factor with category skizofrenia by p value o= 0,012 (p < 0,05).Cinclusion : There is significan correlation between personal conflict factor with category skizofrenia at patient skizofrenia that hospitalized in shed 3th grade RSJD dr RM Soediarwadi Klaten at month may 2004.Key word : personal conflict factor, patient skizofrenia, skizofrenia cases.